The future of open access in Croatia: a survey of academic and research libraries - Hebrang Grgić, Ivana (Array, 2011)
Purpose – The purpose of this research paper is to present Croatian librarians' awareness about the importance of institutional open access (OA) repositories. Design/methodology/approach – The research is based on an online questionnaire sent to all the Croatian research and academic libraries. Online questionnaire was chosen as the most appropriate tool, as the authors wanted it to be anonymous and as quick as possible. Findings – The findings indicate that all the academic librarians in Croatia are aware of the importance of institutional OA repositories. The number of OA repositories in Croatia is rather small, but the librarians are making lots of efforts towards the development of new repositories. Croatian librarians think that the most appropriate software is open-source software ; that OA repositories have to be open access initiative protocol for metadata harvesting compliant ; that copyright owner's consent for archiving is necessary. The biggest problems are the lack of administration support and the researchers' unawareness of the benefits of OA, especially OA repositories. Practical implications – Based on this research, some steps regarding OA could be done on a national level, e. g. guidelines for establishing OA repositories could be created and the obligation of self-archiving should be regulated. This research could be a valuable tool for developing new OA repositories. Originality/value – The paper contributes to the understanding the OA movement in transitional countries and peripheral scientific communities. The knowledge created in such countries can be beneficial for the global scientific community, and OA repositories are valuable way for promoting that knowledge.